The imprinting effect of initial conditions on the configuration of dual distribution in franchising companies - Youngeun Chu; Woojin Yoon (Journal of Innovation & Knowledge (JIK), 2020)
This study aims to conceptualize how the initial conditions of firms at the start of franchising affect the equilibrium level of franchising. Based on the study of dual distribution, we suggest testable propositions. The equilibrium proportion of franchised units in a chain might depend on the initial and current system size, the initial capital, and the degree of geographical dispersion. Also is proposed the moderating effect of age between the equilibrium proportion of franchised units in a chain and the initial system size, the initial capital and the degree of geographical dispersion.
Keywords: 650; Dual distribution; Franchising company; Imprinting effect